ESG Disclosure and Firm Value Dynamics through Financial Performance - Amelia, Rizky; Puspitasari, Diana; Nur Chasanah, Amalia; Prawitasari, Dian (Journal Economic Business Innovation, 2026)
Purpose—This study examines how environmental, social, and governance (ESG) disclosure affects firm value. It also assesses the moderating roles of profitability and leverage in the relationship between ESG disclosure and firm value. Design/methodology/approach—This study adopts a quantitative explanatory approach. The sample comprises 61 manufacturing firms listed on the Indonesia Stock Exchange from 2021 to 2023, yielding 183 firm-year observations selected through purposive sampling. ESG disclosure is measured using Bloomberg ESG scores. Firm value is proxied by price-to-book value, profitability by return on assets, and leverage by the debt-to-equity ratio. Data are analyzed using Partial Least Squares Structural Equation Modeling in SmartPLS. Findings—ESG disclosure has a positive and significant effect on firm value. Profitability strengthens the relationship between ESG disclosure and firm value, suggesting that financially stronger firms provide more credible ESG signals to investors. Leverage also moderates the ESG disclosure–firm value relationship, though its effect is weaker than that of profitability. Originality/value—This research contributes to ESG and corporate finance literature by examining how profitability and leverage serve as moderating factors in the relationship between ESG disclosure and firm value. It emphasizes that the significance of ESG disclosure for firm value is influenced by financial performance and capital structure. Implications—The results indicate that companies should boost their ESG transparency, ensure robust profitability, and optimize leverage to increase market valuation.